Towards Development of a Suitable Protocol for Regeneration of Gladiolus (Gladiolus grandiflorus L.) in-vitro - Maitra, S.; Roychowdhury, N.; Ghosh, P. D.; Satya, P. (International Journal of Bio-resource and Stress Management, 2011)
The effect of different plant growth regulators on growth and development of gladiolus in-vitro using cormlets as explants was studied in two consecutive years. MS medium supplemented with Kinetin had greater efficiency on regeneration of gladiolus cormlets at the concentration of 2 mg L-1. About 90% regeneration of cormlets was obtained by this medium, which started 6.50 days after inoculation to this medium. Among the eight different regeneration media, cormlets cultured on MS medium containing GA3 @ 2 mg L-1 showed the earliest sign of proliferation (5.90 days after inoculation) followed by the medium containing GA3 @ 1 mg L-1 and Kinetin @ 2 mg L-1. After 15 days of culture, the maximum shoot length (5.22 cm) was obtained form the cormlets cultured on MS medium supplemented with GA3 @ 2mg L-1. But IBA proved inhibitory for shoot regeneration of gladiolus from cormlet explants. On the other hand IBA had an effective role on rooting of well-sprouted cormlets and NAA showed a synergistic effect on it. MS medium supplemented with NAA (2 mg L-1) + IBA (2 mg L-1) initiated rooting earliest (6.92 days after transfer). At the time of transfer to the soil, root number and length was found highest with that particular medium (7.43 roots of 48.48 mm/culture). So this medium is recommended for rooting of gladiolus plantlets grown in-vitro.